Analysis of Male and Female Language Features of Harry Potter and the Goblet of Fire Novel - Adzkia Nafida Zahra; Sya’baningrum Prihhartini (Humanitatis : Journal of Language and Literature, 2023)
Gender differences can affect the use of language and socially divide it into male and female language. This study aims to analyze female and male language features spoken by male and female characters in Harry Potter and the Goblet of Fire novel and the social contexts that causes differences in language use in that fictional story using Coates’s (2016) theory of language features and Holmes’s (2013) theory of language and social context. An explanatory sequential mixed methods design was used through two stages to collect and analyze data; quantitative and qualitative. The results show that the dominant female language feature is hedge while the male ones are command and directives. However, there are cross-gender, or shared language features in both male and female languages: hedges, tag questions and questions found in male language features; and commands, directives, swearing and taboo language found in female language features. The results indicate that the use of cross-gender language features can be caused by the social context during the conversation. Those social contexts are social distance, status, formality and functionality.